(untitled) (World Economics and Finance Bulletin, 2024)
This article is aimed at researching and developing a unified digital transport and logistics intelligent platform based on the national operator infrastructure. In the context of the rapid development of the transport and logistics sector, the creation of this platform is an important strategic initiative.